The Identification of Faults using Magnetic Method in Kulonprogo, Yogyakarta, Indonesia - Sorja Koesuma; Sehah Sehah; Choirul Singgih Munandar (Department of Physics, Sebelas Maret University, 2024)
The aims of this study to identify faults and identify subsurface lithology using magnetic anomaly data in the Kulonprogo. In the acquisition was carried out using a Proton Procession Magnetometer (PPM) Geotron G5 with 62 measurement points and a distance of ±1 km between point. Measurements were made on Kebobutak (Tmok), Aluvium (Qa), Andesit (a), and Sentolo (Tmps) formations. The total magnetic field data processing is done with several correction, namely diurnal correction, IGRF, reduce to equator, upward continuation at an altitude of 2000 m, and reduce to pole, and 2D modelling using the forward modelling method. The result of the analysis obtained magnetic field anomaly values in the range of values -400 to 950 nT. The 2D modelling shows that the research area is composed of 4 dominating rock types, namely andesite rock with a susceptibility value of 94 x 10-3, andesite breccia rock with a susceptibility value of 29 x 10-3, clay rock with a susceptibility value of 0,013 x 10-3, and sandstone with a susceptibility value of 5 x 10-3. The identification result show the existence of faults line on Mount Watuaglik, Mount Kamal, and Mount Bodag.